United Kingdom : Financial Sector Assessment Program-Property Markets and Financial Stability-Technical Note. - International Monetary Fund. Monetary and Capital Markets Department (Washington, D.C. : International Monetary Fund, 2016)
The main purpose of this paper is to assess the risks to the financial sector that currently emanate from the United Kingdom property markets. The interaction of property markets with financial markets has important implications for financial stability. Cycles in the prices of housing and commercial property affect the balance sheets of households, banks, and other financial institutions. Excessive lending and price swings in property markets can cause significant distress to both borrowers and lenders. A drop in prices of real property weights on firms' access to finance, which can reduce economic activity, leads to further declines in asset prices and potential financial stability risks.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet